Improving The Quality of Student Learning Through Time Management Training: An Experimental Research - M. Holili; Shafa MF; Faizatul Widat; Feriska Listrianti; Ahmad Walid (Educazione: Journal of Education and Learning, 2024)
This study aims to explore and test the effectiveness of time management training in improving the quality of student learning at SMP Negeri 1 Proppo. The primary focus of the research is how time management techniques such as prioritization, scheduling, execution, and evaluation can help students manage their time more effectively and improve their academic performance. This study uses a qualitative approach with a descriptive type, where data is collected through in-depth interviews, participatory observations, and documentation. Data analysis was done using thematic analysis methods to identify the emerging main patterns and themes. The results show that time management training has a significant positive impact on students' ability to manage time and improve the quality of their learning. Students participating in the training feel more organized, focused, and productive in completing their tasks. These findings are in line with the theory of self-regulated learning and time management, which emphasizes the importance of self-regulation and efficient time allocation in achieving high academic achievement. This study implies that time management training programs should be integrated into school curricula to help students develop essential time management skills from an early age.